Applying Indigenous Knowledge in Education for Lifelong Skills Development and Student Empowerment - Youssef Mohamed Farouk (PT. Islamic Research Publisher, 2025)
This study examines the integration of indigenous knowledge into contemporary education as a strategic approach to fostering lifelong skills development and student empowerment. The research aims to analyze how indigenous knowledge is conceptualized and incorporated into modern curricula, identify pedagogical models that effectively support lifelong learning competencies, and evaluate the impact of such integration on students’ agency, critical thinking, and socio-cultural awareness. Addressing the growing need for culturally responsive and contextually relevant education, this study positions indigenous knowledge as a vital epistemological resource rather than a peripheral cultural element. Methodologically, the study employs a qualitative comparative approach, drawing on document analysis, case studies, and a systematic review of scholarly literature across diverse educational contexts, particularly in the Global South and European settings. Data were analyzed using thematic analysis to identify patterns in curriculum design, instructional strategies, and learning outcomes associated with indigenous knowledge integration. The analytical framework is informed by culturally responsive pedagogy and lifelong learning theory. The findings reveal that the integration of indigenous knowledge enhances the development of transferable skills, including critical thinking, problem-solving, collaboration, and adaptive learning. It also strengthens student empowerment by fostering a sense of identity, agency, and community engagement. However, the study identifies several challenges, including limited institutional support, insufficient teacher training, and the marginalization of indigenous epistemologies within standardized curricula. In response, the study proposes a hybrid pedagogical framework that combines contextual learning, participatory approaches, and transformative education principles. This research contributes to the growing body of literature on culturally grounded education by offering a comparative and integrative perspective that bridges traditional knowledge systems with modern pedagogical practices. It provides practical and theoretical insights for policymakers, educators, and curriculum developers seeking to design inclusive and sustainable education systems aligned with global competencies while preserving local cultural identities.